Efektivitas Discovery Learning Berorientasi Video Microlearning dalam Meningkatkan Keterampilan Berpikir Kritis Siswa - Mahardika, Sekar Putri; Hidayati, Siti Nurul; Aulia, Ernita Vika (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to analyze the critical thinking skills of class VIII-I students at SMP Negeri 1 Sampang before and after implementing Discovery Learning which is stimulated by microlearning. Apart from that, this research was conducted to increase knowledge regarding efficient learning models used to improve critical thinking skills.Method – This research uses a quantitative approach with a pre-experimental design research type. The design used is One Group Pretest-Posttest Design. Data were analyzed using quantitative descriptions with the N-Gain data analysis technique which was then categorized using the criteria table by Hake 1998.Findings – Based on research results, the video-oriented microlearning Discovery Learning model can improve students' critical thinking abilities. This can be seen from the N-Gain results on three indicators which have increased to the high category, namely the basic support indicators, prior clarification, and strategy and tactics. However, there are still two indicators that have increased only with moderate criteria, namely the basic clarification and inference indicators. So further research is needed to find out how long it takes to apply the model until all critical thinking indicators are in the high category. Research Implications – The application of microlearning to the Discovery Learning model stimulation provides excellent implications in increasing student activity in science learning. The research results show that the use of microlearning videos in the Discovery Learning stimulation model is effective in improving junior high school students' critical thinking abilities. It is recommended that further research optimize the learning process and conduct research in more than three meetings for maximum results. This model can also be used in other chapters and subjects that require critical thinking skills.